2019
DOI: 10.1002/jclp.22821
|View full text |Cite
|
Sign up to set email alerts
|

From intention to action: A mixed methods study of clients’ experiences of goal‐oriented practices

Abstract: Objectives Goal‐oriented practices are central to many contemporary psychotherapies. The aim of this study was to explore clients’ experiences of this work. Design Mixed methods, with a main qualitative part and a smaller quantitative component. Participants were 22 clients in integrative psychotherapy (15 females, 6 males, 1 other). Semi‐structured interviews after session 4 and at endpoint were analyzed thematically. On the basis of the identified themes, “goal attitude” scores were developed and their corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 48 publications
(67 reference statements)
6
33
0
2
Order By: Relevance
“…However, all become meaningless if they are not used in meaningful and considered ways with young people. Research into patient feedback on the use of goal-based outcome measures in psychotherapy settings concluded that the key element to using this type of measure is that they are individually tailored and collaboratively used (Di Malta et al, 2019). Measuring outcomes must be of clinical utility and not just a tick-box process (Wolpert et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…However, all become meaningless if they are not used in meaningful and considered ways with young people. Research into patient feedback on the use of goal-based outcome measures in psychotherapy settings concluded that the key element to using this type of measure is that they are individually tailored and collaboratively used (Di Malta et al, 2019). Measuring outcomes must be of clinical utility and not just a tick-box process (Wolpert et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…It would be important for future research to investigate how therapists facilitate future‐orientation, and clients receive such initiatives, in approaches to therapy in which goals are articulated in a more specific and overt manner. In a study of clients’ experiences of explicit goal‐oriented practices, grounded in collaborative discussion of client responses to goals forms, clients reported helpful aspects, such as being helped to move from intention to action through increased awareness, focus, and progress monitoring, but also hindering aspects, such as reduced awareness of their intentions, and a sense of irrelevance, disorientation, and demotivation (Di Malta et al, 2019). According to clients’ reports, the effectiveness of the goal‐oriented practices depended on flexibility and collaboration, as well as having sufficient time to explore and set relevant goals (Di Malta et al, 2019), which correspond to the present therapists’ various devices of constant alignment to clients’ directionality.…”
Section: Discussionmentioning
confidence: 99%
“…Driven by an intention to generate knowledge that is more directly applicable to practice, research has moved in the direction of identifying specific and concrete therapist actions that either facilitate or inhibit productive therapeutic work around goal clarification, negotiation and attainment. This line of research has encompassed the development of measures of alliance‐building behavior (Owen et al, 2013), qualitative studies of client and therapist experience of key processes in the development of collaborative working relationships (Di Malta et al, 2019; Lavik et al, 2018), and analyses of conversational sequences and strategies used by therapists to enable therapeutic tasks and goals to be jointly addressed (von der Lippe et al, 2019; Muntigl et al, 2012; Oddli & Rønnestad, 2012; Oddli et al, 2014; Voutilainen et al, 2010). A central theme across all of these different types of studies has been the emergence of an understanding of the importance of therapist nurturing and encouragement of client agency as a process that contributes both to the construction of a collaborative relationship and to goal accomplishment.…”
Section: Introductionmentioning
confidence: 99%
“…Of those who did engage in the process, most felt that therapeutic benefit was likely to be achieved from working with the client on their goals. As Di Malta et al (2019) suggest, a collaborative therapeutic relationship is important in enabling the process of goal setting. It seemed here that as the client worked with the therapist to define goals which were concrete and motivational, something more was achieved than may otherwise have been generated from self-reflection alone, (see Tryon et al, 2018).…”
Section: Discussionmentioning
confidence: 99%